1992
DOI: 10.1149/1.2069374
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Alkaline Manganese Dioxide Batteries: I . In Situ X‐Ray Diffraction Investigation of the (EMD‐Type) Insertion System

Abstract: flow employed. In no way has the selection of porous structure, cell or flow geometry been optimized; these should be subjects of future investigations. ConclusionsThis study has demonstrated the feasibility of the electrochemical reduction of EAQ dissolved in an organic solvent from an aqueous-continuous suspension flowing past an electrode. With a sufficiently high degree of turbulence, current densities and current efficiencies of industrial interest can be achieved. Although the present results are insuffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 21 publications
(74 reference statements)
5
61
0
Order By: Relevance
“…This behavior is expected given that during these half-cycles the underlying unit cell undergoes either contraction (charging) or expansion (discharge) and this directly influences the hop distance (and hence rate of diffusion) between adjacent oxygen sites. 12,13,15 Comparing the behavior of all three electrodes, we observe comparable behavior during initial oxidation, followed by a subtle drop-off in A √ D for the additive containing electrodes during the latter stages of the first discharge half-cycle (D1). Subsequent charging (C2) reveals clear inhibition of proton diffusion for the additive electrodes, and this feature is further evidence during the second discharge half-cycle.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…This behavior is expected given that during these half-cycles the underlying unit cell undergoes either contraction (charging) or expansion (discharge) and this directly influences the hop distance (and hence rate of diffusion) between adjacent oxygen sites. 12,13,15 Comparing the behavior of all three electrodes, we observe comparable behavior during initial oxidation, followed by a subtle drop-off in A √ D for the additive containing electrodes during the latter stages of the first discharge half-cycle (D1). Subsequent charging (C2) reveals clear inhibition of proton diffusion for the additive electrodes, and this feature is further evidence during the second discharge half-cycle.…”
Section: Resultsmentioning
confidence: 71%
“…14 The rechargeable performance of EMD is in turn limited by the reversibility of this expansion/contraction process. Mondolini et al 15 studied this process in detail and showed that the lattice parameters of γ-MnO 2 are fully recovered if the degree of reduction is controlled to less than the mid-point of the first electron reduction (MnO 1.75 ). However, if reduction proceeds beyond this point the underlying lattice structure is not retained and a slow and steady loss in capacity follows.…”
mentioning
confidence: 99%
“…Although MnO 2 has a high theoretical capacity (∼308 mAh⋅g ‐1 ) within one‐electron cycling in rechargeable battery, the cycle life usually suffers from a big discount at 100% depth of discharge (DOD) due to its unrecoverable crystallographic distortion . When the DOD exceeded to 50%, its capacity retention is usually less than half of the initial value upon 50 to 100 cycles ,. To extend the cycle life of MnO 2 , the cycling has to be implemented at a shallow DOD.…”
Section: Introductionmentioning
confidence: 99%
“…non-rechargeable) alkaline household batteries, highlighting its main problem; poor rechargeability. Several papers discuss strategies to improve its cycleability in alkaline batteries, such as by adding dopants (10,11) or limiting its discharge potential (12,13).…”
Section: Introductionmentioning
confidence: 99%